2021
DOI: 10.3389/fimmu.2021.653205
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus Regulates Caenorhabditis elegans Cell Signaling to Combat Salmonella Infection

Abstract: Salmonella typhimurium DT104 infection causes the death of Caenorhabditis elegans, which can be prevented by certain Lactobacillus isolates. However, the molecular mechanisms of both the host response to the infection and the protection by Lactobacillus are largely unclear. The present study has investigated the life-span and gene expression of both wild-type (WT) and mutants in some key components of cell signaling in response to S. typhimurium infection and protection from Lactobacillus zeae. The results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
3
10
0
Order By: Relevance
“…In this current study, the yeast KT000032 revealed substantial colonization efficiency at different feeding states with negligible differences. These results showed many similarities with the previous reports that showed that different lactic acid bacterial strains possess different attaching and colonization efficiency in C. elegans gut [ 30 ]. The correlation between colonization and hydrophobicity was reported by chelliah et al [ 31 ], but some studies showed no correlation between the two functional properties [ 32 ].…”
Section: Resultssupporting
confidence: 90%
“…In this current study, the yeast KT000032 revealed substantial colonization efficiency at different feeding states with negligible differences. These results showed many similarities with the previous reports that showed that different lactic acid bacterial strains possess different attaching and colonization efficiency in C. elegans gut [ 30 ]. The correlation between colonization and hydrophobicity was reported by chelliah et al [ 31 ], but some studies showed no correlation between the two functional properties [ 32 ].…”
Section: Resultssupporting
confidence: 90%
“…Thus, we conclude that the feeding LPJBC5 activated skn-1 through the p38 MAPK signaling pathway to extend longevity in worms. This result is in accordance to the recent study by Zhou et al [ 60 ].…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, loss-of-function mutants for the nsy-1, sek-1, pmk-1, abf-3 and lys-7 genes are insensitive to the antipathogenic effect of L. zeae. According to the authors, these results suggest the bacterium can regulate the host cell signaling via p38 MAPK pathway (Zhou et al, 2021). A similar conclusion was also advanced by the work of Dinić et al (2021) which showed that administration of the heat-inactivated probiotic strain Lactobacillus curvatus BGMK2-41 induced a PMK-1/p38 MAPK-dependent transcription of C-type lectins (clec-85, clec-172), lysozymes (lys-1, lys-3, lys-5, lys-8) and tight junction protein CLC-1.…”
Section: Discussionmentioning
confidence: 94%
“…Current work has enabled us to demonstrate that daf-16 and sek-1 functionalities are required for L. rhamnosus Lcr35 ® to exert its anti-C. albicans activity, in knockout mutants for these genes, the protective effect being abolished. Recently, Zhou et al (2021) investigated the anti-Salmonella Typhimurium DT104 capacities of Lactobacillus zeae LB1 using a preventive approach. They thus highlighted the overexpression of genes such as daf-16 (insulin pathway), tir-1, sek-1 and pmk-1 (p38 MAPK pathway) and clec-60, sod-3 and skn-1 (other defense molecules) in the presence of the lactobacillus.…”
Section: Discussionmentioning
confidence: 99%